2020
DOI: 10.1007/s10570-019-02939-3
|View full text |Cite
|
Sign up to set email alerts
|

Alkali treatment of hemp fibres for the production of aligned hemp fibre mats for composite reinforcement

Abstract: The main objective of this study was to produce aligned hemp fibre mats from high strength hemp fibres using dynamic sheet forming (DSF). Alkali treatment of hemp fibre was carried out at ambient and high temperature to separate fibres. Single fibre tensile testing was used to assess the tensile properties of the fibres. It was found that the highest tensile properties were exhibited by high temperature treated fibre, whereas the tensile properties exhibited by ambient temperature treated fibre were lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Alkali treated hemp fibres were used to produce fibre mats. The alkali treatment and characterisation of fibres have been detailed in a previously published work [8]. The fibres had an average length and an average diameter of 1.88 mm and 0.05 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkali treated hemp fibres were used to produce fibre mats. The alkali treatment and characterisation of fibres have been detailed in a previously published work [8]. The fibres had an average length and an average diameter of 1.88 mm and 0.05 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A program was written in MATLAB to obtain the FWHM. [8]. Table 2 shows the stacking arrangements of the fibre…”
Section: Assessment Of Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the two different alkali treatments (high temperature and ambient temperature) for hemp fibres, it has been reported that most of the high temperature treatments maintained or increased the fibre tensile strength (or reduction reported for tensile strength was lower) compared to that of untreated fibre, whereas most reported ambient temperature treatments reduced the fibre tensile strength [40]. The removal of weak components has explained the increase in tensile strength of the high temperature treated fibre, and thus, the remaining material is stronger.…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…Regarding process yields, soft NaOH treatments involve lower waste generation, which is a goal of the circular economy and agrees with the principles of green chemistry [ 29 ]. The fiber’s morphology is also affected by lignin removal, since fiber individualization is promoted, achieving higher aspect ratios and contributing to the enhancement of the mechanical properties [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%